Comparison of real costs in the French healthcare system in newly diagnosed patients with pemphigus for first‐line treatment with rituximab vs. standard corticosteroid regimen: data from a national multicentre trial. (1st July 2020) - Hébert, V.; Vermeulin, T.; Tanguy, L.; Tedbirt, B.; Mignard, C.; Bénichou, J.; Joly, P.
Summary: Background: Rituximab has been demonstrated to be highly effective as a first‐line treatment for moderate‐to‐severe pemphigus; however, its high cost can be considered a limitation of this treatment. Objectives: To compare direct costs of two regimens, rituximab + short‐term prednisone vs. prednisone alone, tested in the Ritux3 trial. Methods: Patients were randomly assigned to receive 2 g of rituximab and two 500‐mg maintenance infusions at month 12 and month 18 along with low doses of prednisone for 3–6 months, or high doses of prednisone alone tapered over 12–18 months. We estimated the direct costs related to (i) protocol (treatments, consultations, hospitalizations); (ii) unfavourable disease course (relapse); and (iii) adverse events in both treatment groups during a 3‐year follow‐up. Results: Annual individual cost discrepancies related to drugs decreased from +€3597 to −€1589 from the first to the third year, which corresponded to an initially higher cost in the rituximab group, counterbalanced during follow‐up by costs related to treatment of patients with persistent disease activity/relapses in the standard corticosteroid (CS) group. Individual costs relating to treatment of adverse events were higher in the standard CS group (€4352) than in the rituximab group (€2468). Overall, mean individual total cost over the 3 years of follow‐up was €13 997 in the standard CS arm vs. €14 818 in the rituximab arm, corresponding to a difference of €821 more per patient (+6%). Conclusions: First‐line treatment of pemphigus with rituximab results in a slightly greater cost compared with a standard CS regimen. What's already known about this topic Rituximab is the most effective treatment for moderate‐to‐severe pemphigus. Rituximab cost might be considered as a limitation of this treatment. What does this study add? After 3 years of follow‐up, mean individual total cost for a patient with first‐line treatment with rituximab was €14 818 vs. €13 997 with standard corticosteroids (CS), resulting in a slightly higher cost of €821 (+6%). The initially greater cost of rituximab was counterbalanced by costs related to management of flares/relapses in patients treated with a standard CS regimen.